2017
DOI: 10.5897/ajar2017.12443
|View full text |Cite
|
Sign up to set email alerts
|

Financial profitability and resource use efficiency of boro rice cultivation in some selected area of Bangladesh

Abstract: The paper analysed the profitability and resource use efficiency of boro rice cultivation in Bogra district of Bangladesh using farm level survey data of April-May, 2016. In total 103 farmers were selected randomly from the study area. Result based on Farm Budgeting model showed that per hectare variable cost and total cost of production was BDT (Bangladeshi Taka) 57,583 and BDT 71,208 respectively. Average yield was found 4.112 ton which was more than the previous year's national average yield of 3.965 ton. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…ha In order to test the resource use efficiency, the ratio of marginal value product (MVP) to the marginal factor cost (MFC) for each input is computed and tested for its equality to 1 (Sujan et al, 2017).…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…ha In order to test the resource use efficiency, the ratio of marginal value product (MVP) to the marginal factor cost (MFC) for each input is computed and tested for its equality to 1 (Sujan et al, 2017).…”
Section: Empirical Modelmentioning
confidence: 99%
“…The following algebraic equation was developed to assess the costs and returns of potato production (Sujan et al, 2017).…”
Section: Empirical Modelmentioning
confidence: 99%
“…As boro rice is an irrigated crop, a study showed that 78.7% of the lifted water was important for boro rice production which increases irrigation as well as production cost (Dey et al, 2013). Also at the time of considering individual inputs, human labor was found as the largest contributor of expenses of HYV boro rice production in the Bhola district (Sujan et al, 2017;Majumder et al, 2009). However, in opposition, chickpea is a profitable crop, which has low water Int.…”
Section: Introductionmentioning
confidence: 99%
“…He also found that chickpea was more important for small and medium level farmers. Sujan et al (2017) stated that the boro rice cultivation was a profitable crop in Bogura district and the most important factors for boro rice cultivation was human labor, seed, urea, insecticide, and irrigation. Hoque and Haque (2014) studied the economic profitability of boro rice production by using the Cobb-Douglas production function and found that factors like cost of irrigation, insecticide, seed, and human labor showed a significant effect on profitability.…”
Section: Introductionmentioning
confidence: 99%
“…About 58% of the people live in rural areas, and most of the people are involved in agriculture (BBS, 2016). About 75.1% of agricultural land use to grow rice, of which 42.4% was employed in Boro rice production (Sujan et al, 2017). Agriculture contributes 14.79% of the gross domestic product (GDP) of Bangladesh (MoF, 2017).…”
Section: Introductionmentioning
confidence: 99%